Sustained-release voriconazole-thermogel for subconjunctival injection in horses: ocular toxicity and in-vivo studies - Mora-Pereira, Mariano (BMC Vet Res, 2020)
BACKGROUND: Keratomycosis is a relatively common, sight threatening condition in horses, where treatment is often prolonged and costly. Subconjunctival (SCo) injections offer less resistance to drug diffusion than the topical route, resulting in better penetration to the ocular anterior segment. Voriconazole, a second generation triazole antifungal, is effective against common fungal organisms causing keratomycosis. If combined with a thermogel biomaterial, voriconazole can be easily injected in the SCo space to provide sustained drug release. The purpose of this study was to evaluate the drug concentrations in the anterior segment and clinical effects after SCo injections of voriconazole-containing thermogel: poly (DL-lactide-co-glycolide-b-ethylene glycol-b-DL-lactide-co-glycolide) (PLGA-PEG-PLGA) in healthy equine eyes. RESULTS: Voriconazole aqueous humor (AH) and tear concentrations were compared between 6 horses, receiving 1% voriconazole applied topically (0.2 mL, q4h) (Vori-Top) or 1.7% voriconazole-thermogel (0.3 mL) injected SCo (Vori-Gel). For the Vori-Gel group, voriconazole concentrations were measured in AH and tears at day 2 and then weekly for 23 days, and at day 2 only for the Vori-Top group. Ocular inflammation was assessed weekly (Vori-Gel) using the modified Hackett-McDonald scoring system. Ocular tissue concentrations of voriconazole following SCo 1.7% voriconazole-thermogel (0.3 mL) injections were evaluated post euthanasia in 6 additional horses at 3 different time points. Three horses received bilateral injections at 2 h (n = 3, right eye (OD)) and 48 h (n = 3, left eye (OS)) prior to euthanasia, and 3 horses were injected unilaterally (OS), 7 days prior to euthanasia. Voriconazole-thermogel was easily injected and well tolerated in all cases, with no major adverse effects. On day 2, drug concentrations in tears were higher in the Vori-Top, but not statistically different from Vori-Gel groups. For the Vori-Gel group, voriconazole was non-quantifiable in the AH at any time point. Total voriconazole concentrations in the cornea were above 0.5 μg/g (the target minimum inhibitory concentration (MIC) for Aspergillus sp.) for up to 48 h; however, concentrations were below this MIC at 7 days post treatment. CONCLUSIONS: Voriconazole-thermogel was easily and safely administered to horses, and provided 48 h of sustained release of voriconazole into the cornea. This drug delivery system warrants further clinical evaluation.